Juridical Review of Non-Taxable Income Based on Article 7 of Law Number 7 of 2021 concerning Harmonization of Tax Regulations - Hastuti, Indra; Nugrahaningsih, Widi; Santoso, Aris Prio Agus; Pramudya, Andhika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to analyze the provisions regarding non-taxable income based on article 7 of Law No. 7 of 2021 concerning harmonization of tax regulations, as well as the juridical implications of changes to these provisions for Individual Taxpayers. Non-Taxable Income is an income limit that is not subject to tax by the state, which aims to provide tax relief for taxpayers with low income. Law No.7 of 2021 changes the previous Non-Taxable Income provisions in Law No.36 of 2008 concerning income tax. Apart from that, this research recommends the importance of socializing the new Non-Taxable Income provisions, as well as strengthening supervision by the Directorate General of Taxes to prevent misuse of Taxpayer data and regular evaluation of the amount of Non-Taxable Income is also needed so that it remains relevant to developing social economic conditions.